My beloved world - Sotomayor, Sonia, 1954- (Knopf, 2013)
"An instant American icon--the first Hispanic on the U.S. Supreme Court--tells the story of her life before becoming a judge in an inspiring, surprisingly personal memoir. With startling candor and intimacy, Sonia Sotomayor recounts her life from a Bronx housing project to the federal bench, a progress that is testament to her extraordinary determination and the power of believing in oneself. She writes of her precarious childhood and the refuge she took with her passionately spirited paternal grandmother. She describes her resolve as a young girl to become a lawyer, and how she made this dream become reality: valedictorian of her high school class, summa cum laude at Princeton, Yale Law, prosecutor in the Manhattan D.A.'s office, private practice, federal district judge before the age of forty. She writes about her deeply valued mentors, about her failed marriage, about her cherished family of friends. Through her still-astonished eyes, America's infinite possibilities are envisioned anew in this warm and honest book, destined to become a classic of self-discovery and self-invention, alongside Barack Obama's Dreams from My Father"--